Aquinas’s Unsuccessful Theodicy - Roark, Eric (Philosophy & theology, 2006)
In this paper I examine Thomas Aquinas’s attempt at theodicy (the reconciliation of evil in the world with the existence of an all-powerful, -knowing, and -loving God). Aquinas’s theodicy, utilizing the book of Job, maintains that God uses suffering and fear as a method to encourage us to form a loving relationship with Him. I argue that Aquinas’s theodicy fails because an all-loving God would not utilize suffering and fear as a method by which to encourage us to form a loving relationship with Him. As I argue through example, loving relationships between persons are not underwritten on the foundations of suffering and fear, and as such we have no good reason to think that God would use such methods to form His loving relationships.